Upaya Meningkatkan Disiplin Guru Melalui Sistem Reward dan Funishment - Mardiana Mardiana (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The implementation of this class action research departs from the background of the need for renewal in teaching and learning activities carried out both by teachers and by students specifically aimed at achieving the vision and mission of SDN 010143 Perk. Aek Tarum. This study aims to improve teacher discipline through the Reward and Funishment system to support the effectiveness of the teaching and learning process at SDN 010143 Perk. Aek Tarum district Bandar Island academic year 2018/2019. The subjects of this study were elementary school teacher 010143 Perk. Aek Tarum, data is collected through observation, interviews, tests, and study documentation. The data obtained shows that after the implementation of the action in the form of Reward and Punishment, teachers who are late more than 15 minutes are 0, and teachers who are less than 10 minutes late are 9 teachers. The application of rewards and punishments can increase teacher discipline in the classroom at teaching and learning activities at SDN 010143 Perk. Aek Tarum. Keywords: teacher discipline, reward, funishment  Abstrak: Dilaksanakannya penelitian tindakan kelas ini berangkat dari latar belakang perlunya pembaruan dalam kegiatan belajar mengajar baik yang dilakukan oleh guru maupun oleh siswa khususnya yang bertujuan untuk mencapai visi dan misi SDN 010143 Perk. Aek Tarum. Penelitian ini bertujuan untuk meningkatkan disiplin guru melalui sistem Reward dan Funishment guna menunjang efektivitas proses belajar mengajar di SDN 010143 Perk. Aek Tarum kec. Bandar Pulau TP. 2018/2019. Subjek penelitian ini adalah guru SDN 010143 Perk. Aek Tarum, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Data yang diperoleh menunjukan bahwa setelah diadakan penerapan tindakan berupa Reward dan Punishment, guru yang terlambat lebih dari 15 menit adalah 0, dan guru yang terlambat kurang dari 10 menit sebanyak 9 orang guru. Penerapan Reward dan Punishment dapat meningkat disiplin guru hadir didalam kelas pada kegiatan belajar mengajar di SDN 010143 Perk. Aek Tarum. Kata Kunci :  disiplin guru, reward, funishment